Pengaruh Jumlah Produksi Perikanan Tangkap Terhadap PDRB Kota Dumai: Penelitian - Safitri; L.J., Pratama; B., Anugrah; A., Prasetia; M.A, & Rasti; Taryono (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study analyzes the effect of capture fisheries production on the Gross Regional Domestic Product (GRDP) of Dumai City from 2020 to 2024. A descriptive quantitative method was applied using secondary data from the Marine and Fisheries Office and the Central Bureau of Statistics (BPS). The results show that capture fisheries production fluctuated, with a significant increase of 266 percent in 2021 compared to the previous year. The main commodities—shrimp, Lomek, and Bombay duck—jointly contributed more than 20 percent of total production value. On average, the capture fisheries subsector contributed 1.48 percent to Dumai’s GRDP. These findings indicate that capture fisheries hold significant economic potential but require blue economy–based management to enhance value added and ensure sustainable resource utilization.